Integrated Multi-Omic Analyses of the Genomic Modifications by Gut Microbiome-Derived Metabolites of Epicatechin, 5-(4′-Hydroxyphenyl)-γ-Valerolactone, in TNFalpha-Stimulated Primary Human Brain Microvascular Endothelial Cells - Corral-Jara, Karla Fabiola; Nuthikattu, Saivageethi; Rutledge, John; Villablanca, Amparo; Morand, Christine; Schroeter, Hagen; Milenkovic, Dragan (Frontiers in Neuroscience, 2021)
Cerebral blood vessels are lined with endothelial cells and form the blood-brain barrier and their dysfunction constitutes a crucial event in the physiopathology of neurodegenerative disorders and cognitive impairment. Epicatechin can improve cognitive functions and lower the risk for Alzheimer’s disease or stroke. However, molecular mechanisms of epicatechin on brain vascular endothelium are still unexplored. The objective of this study was to investigate the biological effects of gut microbiome-derived metabolites of epicatechin, 5-(4′-Hydroxyphenyl)-γ-valerolactone-3′-sulfate and 5-(4′-Hydroxyphenyl)-γ-valerolactone-3′-O-glucuronide, in TNF-α-stimulated human brain microvascular endothelial cells at low (nM) concentrations by evaluating their multi-omic modification (expression of mRNA, microRNA, long non-coding RNAs, and proteins). We observed that metabolites are biologically active and can simultaneously modulate the expression of protein-coding and non-coding genes as well as proteins. Integrative bioinformatics analysis of obtained data revealed complex networks of genomics modifications by acting at different levels of regulation. Metabolites modulate cellular pathways including cell adhesion, cytoskeleton organization, focal adhesion, signaling pathways, pathways regulating endothelial permeability and interaction with immune cells. This study demonstrates multimodal mechanisms of action by which epicatechin metabolites could preserve brain vascular endothelial cell integrity, presenting mechanisms of action underlying epicatechin neuroprotective properties.